2005
DOI: 10.1038/nature03255
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared images of β Pictoris and the possible role of planetesimal collisions in the central disk

Abstract: When viewed in optical starlight scattered by dust, the nearly edge-on debris disk surrounding the A5V star beta Pictoris (distance 19.3 pc; ref. 1) extends farther than 1,450 au from the star. Its large-scale complexity has been well characterized, but the detailed structure of the disk's central approximately 200-au region has remained elusive. This region is of special interest, because planets may have formed there during the star's 10-20-million-year lifetime, perhaps resulting in both the observed tilt o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
172
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(182 citation statements)
references
References 23 publications
10
172
0
Order By: Relevance
“…Clearly, studying this debris and how frequently it is detected around nearby stars has the potential to inform about terrestrial planet formation processes more generally, as well as the fraction of stars that host such planets (Jackson and Wyatt 2012). Some stars also show evidence that could point to recent giant impacts in the more distant reaches of their planetary systems (Telesco et al 2005;Dent et al 2014;Stark et al 2014), but conclusions remain tentative for now.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Clearly, studying this debris and how frequently it is detected around nearby stars has the potential to inform about terrestrial planet formation processes more generally, as well as the fraction of stars that host such planets (Jackson and Wyatt 2012). Some stars also show evidence that could point to recent giant impacts in the more distant reaches of their planetary systems (Telesco et al 2005;Dent et al 2014;Stark et al 2014), but conclusions remain tentative for now.…”
Section: Introductionmentioning
confidence: 93%
“…While it is possible that the clump in β Pic was created in the break-up of a planetesimal within the last 50 years (Telesco et al 2005), we are many orders of magnitude more likely to witness the same impact in the asymmetric disk phase than in the clump phase. Moreover the morphology, and in particular its wavelength dependence outlined above, are exactly that expected if the asymmetry in the clump is the result of a giant impact witnessed in the asymmetric disk phase; e.g., Fig.…”
Section: Collisions At Larger Separationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that a planet of about 1 M Jup at about 10 AU with a moderate eccentricity of e ≈ 0.05 can explain both the warp of the dust disk and the FEBs phenomenon. More recently, belt structures at about 6.4, 16, 32, and 52 AU were observed (Wahhaj et al 2003;Okamoto et al 2004;Telesco et al 2005;Golimowski et al 2006). Reviewing the evidence of planets in the β Pic disk and using dynamical simulations, Freistetter et al (2007) obtained additional constraints on these planets.…”
Section: Eccentric Orbitmentioning
confidence: 99%
“…The emission is highly asymmetric, with 30% of the emission located in a single clump on one side of the star, with kinematics giving the exact position of the gas clump at 85 AU from the star (Dent et al 2014), possibly colocated with a dust clump detected in the mid-IR (Telesco et al 2005). The radial distribution of CO is similar to the location of the planetesimal belt inferred from the continuum emission to extend 50-150 AU, which is thus thought to be the source of gas.…”
Section: Introductionmentioning
confidence: 99%